Work experience at height suppressed the effect of dynamic visual input on postural sway when static visual cues were visible - Torgerud, Steven R.; Cho, HyeYoung; McGlothlin, James D.; Rietdyk, Shirley (Brazilian Journal of Motor Behavior, 2019)
Background:Balance skills are challenged at the roofing worksite by dynamic visual cues in the form of clouds and trees that move with the wind; any instability may result in a fall from height.Aim:To determine if roofers are less susceptible to a dynamic visual surround (moving room) when stationary cues were available, relative to people who do not work in a similar environment.Methods:Forty male adults participated, including young roofers (N=10,26.3 years), middle-aged roofers (N=10,50.6 years), young controls (N=10,26.2 years) and middle-aged controls (N=10,55.1 years). Center of pressure root mean square (APRMS) was assessed during quiet standing and four moving room conditions when stationary cues were:(1)not in place,(2)in the foreground (inside the moving room),(3)in the background (outside the moving room, but still visible) and (4)in the foreground and background. Results:A workgroup by visual cue interaction was observed (p=0.032), where roofers had up to 18% lower APRMS relative to controls when the background references were in place. The interaction effect was independent of age. Interpretation:The roofers were able to suppress visually-induced postural sway when stationary visual cues were present in the background, likely due to the severe consequences for loss of balance when working at height. The suppression was maintained in aging workers.